Immediate-release supplemental melatonin for delayed sleep phase disorder in children: an overview. (2nd February 2019) - Mantle, David
Abstract : Delayed sleep phase disorder (DSPD) is a sleep disorder commonly affecting children, particularly those with neurological problems, such as autism and attention deficit hyperactivity disorder (ADHD). DSPD is characterised by difficulty in falling asleep, and it results from misalignment of the internal circadian clock with desired sleep time. For those children for whom good sleep hygiene practice is unsuccessful, supplementation with melatonin is standard practice. Randomised controlled studies have shown that strategically timed administration of melatonin, typically in the dose range 3–6 mg, is effective in advancing circadian rhythm and sleep onset in a clinically significant manner. Supplemental melatonin is available in two formulations, immediate-release and controlled-release; for sleep induction as required in DSPD, immediate-release melatonin is considered to be the more effective formulation, as supported by 19 randomised controlled clinical studies (comprising more than 800 individuals), together with a meta-analysis. The safety of supplemental melatonin administration in children, particularly in the short term, has been well documented. Melatonin supplementation is relevant to a number of aspects of neuroscience nursing; in addition to improving sleep onset in children with neurological disorders, melatonin supplementation may be of benefit in intensive care patients following brain injury, in patients with neurodegenerative disorders, and in nurses themselves to counter the detrimental effects of night-shift working.